Plasticity mechanisms of memory consolidation and reconsolidation in the perirhinal cortex - Miranda, Magdalena (2018)
In this review we explore the role of the perirhinal cortex (Prh) in memory, focusing on the cellular and molecular mechanisms that have been described to happen in this structure. The Prh is part of the medial temporal lobe, but the evidences show that it has a different function than that of the hippocampus. In particular, the Prh is known to be important for object recognition memory, although it could have a role in other types of memory. However, despite the fact that object recognition tasks are widely used, information regarding the molecular and cellular mechanisms underlying this type of memory in Prh is lacking. We discuss a series of studies of memory and plasticity in this region and how they might relate. In addition, we propose that Prh could play a role as a “pattern separator” for object memories, similar to the function of the dentate gyrus of the hippocampus in the spatial domain.